2012
DOI: 10.1073/pnas.1207461109
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal nitric oxide contributes to sex difference in affective behaviors

Abstract: Mechanisms underlying the female preponderance in affective disorders are poorly understood. Here we show that hippocampal nitric oxide (NO) plays a role in the sex difference of depressionlike behaviors in rodents. Female mice had substantially lower NO production in the hippocampus and were significantly more likely to display negative affective behaviors than their male littermates. Eliminating the difference in the basal hippocampal NO level between male and female mice mended the sex gap of affective beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…The dependence of male plasticity on NO may relate to baseline differences between the sexes. Females have, within the hippocampus, less abundant NO and reduced NOS1 expression compared with males, although the application of estradiol increases hippocampal NOS1 expression (Hu et al, ). Therefore, a possible explanation for this sex difference is that females lack available NO for the induction of plasticity and thus rely on other molecular pathways instead.…”
Section: Sex Differentiation Of the Role Of α‐Nitric Oxide Synthase‐1mentioning
confidence: 99%
See 2 more Smart Citations
“…The dependence of male plasticity on NO may relate to baseline differences between the sexes. Females have, within the hippocampus, less abundant NO and reduced NOS1 expression compared with males, although the application of estradiol increases hippocampal NOS1 expression (Hu et al, ). Therefore, a possible explanation for this sex difference is that females lack available NO for the induction of plasticity and thus rely on other molecular pathways instead.…”
Section: Sex Differentiation Of the Role Of α‐Nitric Oxide Synthase‐1mentioning
confidence: 99%
“…Recent studies have also demonstrated a role for E2 in inhibition and hve begun to reveal not only that is this sex specific but that E2 acts through distinct molecular pathways. Acute E2 application to hippocampal slices has revealed a rapid suppression of GABAergic inhibitory synaptic transmission at perisomatic inputs to pyramidal cells within the hippocampal CA1, specifically through a molecular cascade including the α form of the estrogen receptor (ERα), metabotrophic glutamate receptor 1 (mGluR1), and endocannabinoid receptor 1 (Huang and Woolley ). Remarkably, this inhibitory effect was evident only in females; E2 had no effect on inhibitory postsynaptic currents (IPSCs) in males (Huang and Woolley ).…”
Section: Role Of Estrogen In Synaptic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, decreased ER β mRNA in postmortem locus coeruleus has been found to correlate with suicide [13], and, even more recently, ER β -mediated hippocampal nitric oxide levels have been implicated in affective behaviors in females, but not males [171]. Neurotransmitter release from these regions influences mood, affect, and stress responses, and E 2 increases the rate of monoamine oxidase degradation and serotonin transport which enhances serotonin at the synapse; E 2 also increases serotonin receptor expression [172, 173].…”
Section: Estrogens and Mood Regulationmentioning
confidence: 99%
“…Previous research has shown that following repeated stress, either restraint stress or unpredictable stress, results in increases in NOS-NO levels in numerous brain regions, including the cortex and hippocampus (Gao et al, 2014;Harooni et al, 2009;Hu et al, 2012;Zhou et al, 2011). It is likely these increases in NO lead to increases in cGMP levels as well (Meyerhoff et al, 1985;Southam and Garthwaite, 1993).…”
Section: Discussionmentioning
confidence: 99%